Enhanced nucleation and growth of HfO2 thin films grown by atomic layer deposition on graphene - Kim, Soo Bin; Ahn, Yeong Hwan; Park, Ji Yong; Lee, Sang Woon (Journal of Alloys and Compounds, 2018)
Nucleation and growth characteristics of HfO2 thin films on graphene are investigated using atomic layer deposition (ALD). Substantial delay (∼70 ALD cycles) in the nucleation of HfO2 films is observed during HfO2 ALD on graphene, which causes large leakage current in Au/HfO2/graphene capacitors at low HfO2 ALD cycles (<200). The nucleation delay in HfO2 ALD decreases significantly to ∼10 ALD cycles with graphene surface treatment using trimethylaluminum (TMA) and H2O. Graphene surface treatment is performed in an ALD chamber prior to the deposition of HfO2 film using TMA and H2O at 150 °C (same as the HfO2 ALD process temperature). With the improvement in the nucleation of the HfO2 films, the leakage current decreases significantly by a factor of 102–105 (at 1 V) than that without surface treatment for a given number of HfO2 ALD cycles. A higher dielectric constant of HfO2 film is achieved using the surface treatment (k ∼14.5) than that without the surface treatment (k ∼5.6). The resistance of graphene increases substantially (ΔR/R0 ∼24%) after the growth of HfO2 films by ALD without surface treatment, indicating degradation of graphene properties. However, the electrical resistance of graphene changes negligibly (ΔR/R0 ∼0.5%) after the growth of HfO2 films with surface treatment, implying a conservation of the carrier mobility of graphene. This indicates the importance of surface treatment on graphene for HfO2 film growth by ALD. Therefore, the graphene surface treatment using TMA and H2O thus enables an achievement of enhanced nucleation and electrical properties of HfO2 films without degrading the mobility of graphene, thus providing promising opportunities in graphene electronics.
Keywords: Electrical resistances; Graphene properties; HfO2; High- k; Nucleation and growth; Process temperature; Substantial delays; Trimethylaluminum; Atomic layer deposition; Graphene; HfO2; High-k; Nucleation